2023
DOI: 10.1111/jcmm.17700
|View full text |Cite
|
Sign up to set email alerts
|

BDH1 promotes lung cancer cell proliferation and metastases by PARP1‐mediated autophagy

Abstract: Lung cancer has become the leading cause of lethal and morbidity in the world. Radical resection is the best treatment of lung cancer.There are dramatic differences in prognosis between patients with surgical and non-surgical treatments. About two thirds of lung cancer patients are newly diagnosed with unresectable locally advanced (IIIB stage) or oligotransduction (IVa stage), which were main limitation factors for radical resection of lung cancer. However, lymph node metastases and distant metastases were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, in the later stages of tumor development, the absence of autophagy may result in the accumulation of mitochondrial defects, ultimately suppressing tumor growth ( Strohecker et al, 2013 ). Various genes and signaling pathways, such as PARP1-mediated AMPK-mTOR, RPL11, COTE-1, PINK1, PEDF, and MALAT1, have been identified to play critical roles in regulating autophagy and influencing lung cancer cell proliferation, migration, and invasion ( Ma et al, 2018 ; Lu et al, 2020 ; Miao et al, 2022 ; Chen et al, 2023 ; Ma et al, 2023 ; Zhang et al, 2023 ). Additionally, certain compounds, such as the metal, Cd, schizandrin A, pinocembrin, adenine aldehyde, and inhibitors of basal autophagy, have been found to induce autophagy in lung cancer cells, affecting proliferation and migration ( Kaminskyy et al, 2012 ; Wang et al, 2020 ; Gong, 2021 ; Zhu et al, 2021 ; Ghemrawi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the later stages of tumor development, the absence of autophagy may result in the accumulation of mitochondrial defects, ultimately suppressing tumor growth ( Strohecker et al, 2013 ). Various genes and signaling pathways, such as PARP1-mediated AMPK-mTOR, RPL11, COTE-1, PINK1, PEDF, and MALAT1, have been identified to play critical roles in regulating autophagy and influencing lung cancer cell proliferation, migration, and invasion ( Ma et al, 2018 ; Lu et al, 2020 ; Miao et al, 2022 ; Chen et al, 2023 ; Ma et al, 2023 ; Zhang et al, 2023 ). Additionally, certain compounds, such as the metal, Cd, schizandrin A, pinocembrin, adenine aldehyde, and inhibitors of basal autophagy, have been found to induce autophagy in lung cancer cells, affecting proliferation and migration ( Kaminskyy et al, 2012 ; Wang et al, 2020 ; Gong, 2021 ; Zhu et al, 2021 ; Ghemrawi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relatórios anteriores indicaram que o BDH1 atua como um regulador crítico em múltiplas doenças, como doença renal diabética, doença hepática gordurosa e câncer. 29 - 31 É importante ressaltar que foi revelado que a superexpressão de BDH1 atenua a apoptose de cardiomiócitos 32 de camundongos induzida por peróxido de hidrogênio. Consistentemente, nosso estudo mostrou que o BDH1 foi significativamente regulado negativamente em células AC16 tratadas com DOX, e a superexpressão de BDH1 suprimiu a apoptose de células AC16 induzida por DOX.…”
Section: Discussionunclassified
“…Previous reports have indicated that BDH1 acts as a critical regulator in multiple diseases, such as diabetic kidney disease, fatty liver disease, and cancer. 29 - 31 Importantly, it has been revealed that BDH1 overexpression attenuates hydrogen peroxide-induced apoptosis of mouse cardiomyocytes. 32 Consistently, our study depicted that BDH1 was significantly downregulated in DOX-treated AC16 cells, and overexpressing BDH1 suppressed DOX-induced AC16 cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%